Strategy To Reduce Traffic Jams On Piet A. Tallo Street, Kupang City - Amy Wadu; A A Tuati; M R Sodanango (U Karst, 2020)
Problems when the flow of traffic on urban roads exceeds the road's capacity, resulting in traffic jams. It happened on the Piet A. Tallo street during peak hour conditions. Especially in converted type of route from 4/2T to 2/2TT, which results in a buildup of traffic flow at that point. This research aims to analyze the volume to capacity ratio (v/c) and provide recommendations for long-term strategies to reduce traffic jams on Piet A. Tallo Street. Traffic flow and capacity analysis based on Guidelines for Indonesia Road Capacity 2014 (PKJI2014), while the projected growth in the number of vehicles in the next 20 years, uses the linear regression method. The results show that peak traffic flow exceeds road capacity in the 2/2TT segment with a v/c ratio of 1.08. Recommendations for handling this by regulating side friction and changing road segment type 2/2TT to 4/2T. Using linear regression projected traffic flow in 2040, road capacity can still serve traffic flow with a maximum v/c ratio of only 0.93.